Amateur basketball injuries. A prospective study among male and female athletes - Stergioulas, A.; Tripolitsioti, A.; Kostopoulos, N.; Gavrilidis, A.; Sotiropoulos, N.; Baltopoulos, P. (Biology of Exercise, 2007)
The purpose of this study was to record injuries in amateur males and females basketaball players. These players participated in a domestic championship in Athens, during the 2000-2001 basketball season. An injury is considered the problem in musculoskeletal system that did not allow the player to continue the game or the training and might be out of the field for at least one day. Every injury was recorded by the coach of the team. From the start of the period until the end of the year 110 injuries in males and 86 in females were recorded. The rate was 0.72 injuries per male athlete per year, while for females the corresponding rate was 0.56. Males had more overuse injuries than females (p 0.02), while females had more injuries in the lumbar spine (p 0.001). Males had more knee sprains in the medial collateral ligament of (p 0.05), while females had more sprains in the anterior cruciate ligament (p 0.005). Both sexes sustained injuries during the games and in the second part. It is concluded that injuries in Greek amateur basketball players did not differ considerably from published studies. Further studies are needed in order that such injuries should be prevented.